Design and synthesis of dinuclear alkynylplatinum(II) terpyridine complexes as sensitizers for light-harvesting. (14th December 2016) - Kwok, Eric Chi-Ho; Chan, Mei-Yee; Wong, Keith Man-Chung; Yam, Vivian Wing-Wah
Graphical abstract: A class of dinuclear alkynylplatinum(II) terpyridine complexes has been successfully synthesized and characterized. These complexes were found to strongly absorb from 280 to 700 nm. The excited state and electrochemical properties of these complexes were studied. The potential applications of these complexes as sensitizers in DSSCs have been explored. Abstract: A class of dinuclear alkynylplatinum(II) terpyridine complexes has been successfully synthesized and characterized, and their photophysical, electrochemical and excited state properties have been revealed. These dinuclear alkynylplatinum(II) terpyridine complexes have been shown to serve as photosensitizers in light-harvesting processes.